Thyroid carcinoma arising from ectopic thyroid tissue - Tridone, Paula; Halligan, Juan J.; Grasso, Lucía; Manassero, Nelson; Peña, Carla (Revista Argentina de Cirugía, 2026)
Ectopic thyroid tissue is characterized by the presence of thyroid tissue in locations other than its usual pretracheal position. We report the case of a 79-year-old asymptomatic male patient who presented with a right lateral neck tumor which had developed within the past four months. The imaging tests were suggestive of thyroid carcinoma with cervical lymph node metastasis. The patient underwent total thyroidectomy and R2 resection of a lateral tumor mass with invasion of deep planes and the primitive carotid artery. The pathology examination of the thyroid gland reported absence of neoplastic cells, and a poorly differentiated papillary thyroid carcinoma with anaplastic focus was observed in the lateral neck tumor. Thyroid carcinoma arising in ectopic thyroid tissue is an extremely rare entity, and a poorly differentiated papillary carcinoma with anaplastic foci is even more uncommon.